Struktur Komunitas Mangrove di Pesisir Teluk Tomini Kabupaten Boalemo Provinsi Gorontalo - Zees, Fauzia; Sulistijowati, Rieny; Mile, Lukman (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Mangroves are coastal ecosystems, especially in tropical areas including Tomini Bay, Gorontalo Province. Mangrove ecosystems not only function as coastal abrasion barriers, natural protection from ocean waves, but also as plants that are beneficial to human life, especially for coastal communities. . This study aimed to identify and analyze the structure of mangrove communities on the coast of Tomini Bay, Boalemo Regency, Gorontalo Province. Data collection was carried out using the line transect method at four observation stations for the seedling and sapling categories., then analyzed to determine the absolute density, absolute frequency, and dominance of species. Mangroves found in Tomini Bay, Boalemo Regency from the four stations consist of A. marina, B. gymnorhiza, B. parviflora, C. decandra, C. tagal, R. apiculata, R. mucronata, R. stylosa, S. alba, S. caseolaris, X. moluccensis. In the seedling category, the C. tagal mangrove species at station 2 (Dulangeya Village) showed the highest value in Boalemo Regency, with an absolute density of 56 ind/m², an absolute frequency of 0.48, and a relative dominance of 87.5%. On the other hand, the B. gymnorhiza species recorded the lowest value compared to all observation stations in Boalemo Regency, with an absolute density of only 1 ind/m², an absolute frequency of 0.05, and a relative dominance of 1.56%. The C. tagal mangrove sapling category at station 2 (Dulangeya Village) had the highest absolute density, absolute frequency, and relative dominance in Boalemo Regency, at 8.36 ind/m2 and 0.71 and 73.85, respectively. R. apiculata had the lowest density of all stations in Boalemo Regency, at 0.04 ind/m2 and 0.05 and 0.35, respectively